JURIDICAL ANALYSIS AGAINST THE DISMISSAL POSITION OF CHAIRMAN THE CONSTITUTIONAL BASED ON THE RULING OF HONORARY COUNCIL OF THE CONSTITUTIONAL COURT NUMBER: 2/MKMK/L/11/2023: Constitutional Court - Putra, Irwan Sapta (Program Magister Ilmu Hukum, STIH Painan, 2024)
This article examines the decision made by the honorary panel of the Constitutional Court regarding reports of violations of the code of ethics for constitutional judges made by Deni Inriyani against the chairman of the Constitutional Court, Anur Usman, who is the brother-in-law of the President of the Republic of Indonesia, namely Mr. Jokowi. Previously, the chairman of the Constitutional Court issued Decision Number 90/PUU-XXI/2023, the contents of which stated Article 169 letter q of Law Number 7 of 2017 concerning General Elections (State Gazette of the Republic of Indonesia of 2017 Number 182, Supplement to State Gazette of the Republic of Indonesia Number 6109 ) which states,